Winter Description And Symbolic Meaning In Uzbek Poetry - Sohibova Zarnigor Nusratilloyevna (Universitas Muhammadiyah Sidoarjo, 2022)
The artistic interpretation of the seasons in his poetry has deep roots. In the poetry of classical and modern poets, the poetic depiction of the seasons is associated with human life, the reflection of the lyrical hero's psyche, as an important means of drawing philosophical conclusions from the poetic work. This article analyzes the poems dedicated to the winter season and reveals the harmony between the natural landscape and the human psyche in this season.